2006
DOI: 10.1007/s00359-006-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the G-protein α-subunit gustducin in mammalian spermatozoa

Abstract: Although chemotaxis has been proposed to guide sperm to egg throughout the animal kingdom, sperm attractants released from mammalian eggs have not been identified. Since the G protein subunit alpha-gustducin is accepted as a marker of chemosensitive cells, attempts were made to explore whether alpha-gustducin is also expressed in spermatozoa of mammals. Immunohistochemical approaches using an anti-alpha-gustducin-specific antibody revealed the most intense immunoreactivity in differentiating spermatids. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 63 publications
6
27
0
Order By: Relevance
“…S1 and S2). In agreement with a previous study (28), we found that Tas1r2 mRNA is also expressed in the same cells ( Fig. 1 B and E; Fig.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…S1 and S2). In agreement with a previous study (28), we found that Tas1r2 mRNA is also expressed in the same cells ( Fig. 1 B and E; Fig.…”
Section: Resultssupporting
confidence: 94%
“…We also detected mRNAs for Tas1r3 and Tas1r2 in mature spermatozoa stored in the epididymis. These data are in agreement with previous reports showing GNAT3, TAS1R1, TAS1R2, and TAS1R3 in testis and in sperm (27)(28)(29)(30). It is noteworthy that TAS2R receptors that respond to bitter compounds in taste cells also are expressed in these postmeiotic cells (47,48).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Immunoelectron microscopic analysis was performed using immersion fixed mouse testis tissue as described in detail before (Fehr et al, 2007). The fixation solution consisted of 1.25% pformaldehyde, 0.5% glutaraldehyde and 0.025% picric acid in 0.1 M sodium cacodylate buffer (pH 7.3).…”
Section: Immunoelectron Microscopymentioning
confidence: 99%